Phenomenological Inquiry into EFL Tertiary Students’ Experiences of Academic Culture in the Pertukaran Mahasiswa Merdeka (PMM) Program - Musdalifah; Andi Rachmawati Syarif; Muflihun (International Journal of Research in Education, 2025)
The Pertukaran Mahasiswa Merdeka (PMM) program, part of the Merdeka Belajar Kampus Merdeka (MBKM) initiative, offers EFL students the opportunity to engage in diverse academic and cultural environments across Indonesia. This research aims to explore the academic cultural experiences of three EFL students who participated in the PMM program, focusing on their cross-cultural adaptation and personal development. The research subjects were students who had participated in the PMM program and were enrolled in the English Language Education program at two different universities in Southeast Sulawesi. Based on Kim's (2015) theory of cross-cultural adaptation, this study utilized a descriptive qualitative design with a phenomenological approach. Data were collected through semi-structured interviews and analyzed thematically using an interactive model of data reduction, display, and inference. The findings of this study reveal a dynamic process of stress, adaptation, and personal growth, as university students navigate cultural, linguistic, and academic differences. Key challenges included language barriers, culture shock, and unfamiliar academic norms, which resulted in initial stress. However, the students actively adopted strategies such as social observation, intercultural communication, and flexibility in response. This research highlights the important role of social support from peers, lecturers and the community in promoting adaptation and building confidence. In addition to overcoming external challenges, the students developed deeper intercultural competence, empathy, self-reflection, and professional readiness as future educators. This growth highlights the interplay between cross-cultural adaptation and identity formation, which offers new insights into the role of PMM programs in shaping holistic and inclusive educational practices in Indonesia.